Optimised conditions for Pulsed Field Gel Electrophoresis (PFGE) separations of Pasteurella multocida B:2 DNA - Hasima, N.N.; Saidi, J.; Thong, Kwai Lin; Ansary, A. (Malaysian Society for Molecular Biology and Biotechnology, 2001)
Pulsed-field condition specific for Pasteurella multocida B:2 have been optimized to obtain a good separation resolution. Restriction enzyme, NotI, was the most suitable as it generates discernible number of bands. Other optimised electrophoretic conditions were: 1.5% agarose gel concentration, 200V, ramped pulse time of 1-25 s, and a runtime of 26 h. This research is important for fast and accurate characterisation of this bacterial strain following an outbreak in Malaysia.